1997
DOI: 10.1159/000109701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multiple Sclerosis in Bulgaria

Abstract: The previously reported prevalence of multiple sclerosis in Bulgaria is considerably lower than that reported for neighbouring countries. The aim of this study was to perform a detailed epidemiological investigation in well-defined populations in this country to obtain an accurate estimate of the frequency of multiple sclerosis. An epidemiological study was conducted in two small areas of the country. All patients with clinically or laboratory-supported, definite multiple sclerosis according to Poser''s criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 1 publication
3
12
3
1
Order By: Relevance
“…However, when the two studies are compared after age and gender adjustment, these differences (MS rates and demographic characteristics, such as age, of both groups) become insignifi cant. The prevalence rate and average age of patients in this study was much higher than in our study, and was also higher than epidemiological studies carried out in neighboring countries (11)(12)(13)(14)(15)20).…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…However, when the two studies are compared after age and gender adjustment, these differences (MS rates and demographic characteristics, such as age, of both groups) become insignifi cant. The prevalence rate and average age of patients in this study was much higher than in our study, and was also higher than epidemiological studies carried out in neighboring countries (11)(12)(13)(14)(15)20).…”
Section: Discussioncontrasting
confidence: 81%
“…We therefore believe that the prevalence rate detected in our study is broadly consistent with the actual prevalence rate in the study region. Similar prevalence rates were reported for neighboring countries (10,11,13). Yet, it is still possible that different prevalence rates may be found in different regions in Turkey, as ethnic backgrounds are heterogeneous throughout the country.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…org/news-messages/ms-registry-and-national-representation/). The literature search found only 16 studies, of which the last epidemiology study was in 1997 (33), and reported a considerably lower prevalence of MS in Bulgaria comparing with the neighboring countries.…”
Section: % Of Patientsmentioning
confidence: 99%